2003
DOI: 10.1590/s0100-46702003000200009
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and electrochemical characterization of Pt nanoparticles dispersed on niobium oxide

Abstract: Electrodes consisting of Pt nanoparticles dispersed on thin films of niobium oxide were prepared onto titanium substrates by a sol-gel method. The physical characterization of these electrodes was carried out by X-ray diffraction, scanning electron microscopy and energy dispersive X-ray analysis. The mean size of the Pt particles was found to be 10.7 nm. The general aspects of the electrochemical behavior were studied by cyclic voltammetry in 1 mol L -1 HClO 4 aqueous solution. The response of these electrodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…An inhouse electrochemical cell was designed for this measurement, with a ZnSe window, which allows the detection of the three bands associated to the typical oxidation products of ethanol. The yield of oxidation products was calculated using the respective integrated band intensities (A i ), and the amount of a given species Q i (mol cm -2 ) inside the thin layer cavity followed the relationship (16) shown in equation 1, where ε effi is the value of the effective absorption coefficient (3.5•10 4 M -1 cm -2 for CO 2 , 5.8•10 3 M -1 cm -2 for acetic acid, and 2.2•10 3 M -1 cm -2 for acetaldehyde).…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…An inhouse electrochemical cell was designed for this measurement, with a ZnSe window, which allows the detection of the three bands associated to the typical oxidation products of ethanol. The yield of oxidation products was calculated using the respective integrated band intensities (A i ), and the amount of a given species Q i (mol cm -2 ) inside the thin layer cavity followed the relationship (16) shown in equation 1, where ε effi is the value of the effective absorption coefficient (3.5•10 4 M -1 cm -2 for CO 2 , 5.8•10 3 M -1 cm -2 for acetic acid, and 2.2•10 3 M -1 cm -2 for acetaldehyde).…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…Dispersion of Pt particles into an oxide matrix can lead, depending mainly on the oxide nature, to a Pt-modified oxide with better catalytic properties than pure Pt. For instance, Pt−WO x nanophases have shown an enhanced activity for the oxidation of methanol, while a significant enhancement for CO and methanol oxidation was reported for electrodeposited Pt nanoparticles on IrO 2 films . Some of us have shown that samples of different compositions containing Pt nanoparticles dispersed on RuO 2 layers also present a considerable activity for methanol oxidation .…”
Section: Introductionmentioning
confidence: 99%
“…Herbicides are pesticides that are used to kill or slow the growth of weeds. They were categorized based on their activity (contact or systemic), use (soil, pre-emergent or post-emergent) and mode of action on plant biochemical mechanisms [91,92]. In addition, their target is classified as non-selective (kills all surrounding plants) or selective (attacks only weeds and leaves the crop alone) [93].…”
Section: Cvs Of 50 μM Indigo Carmine At Seo 2 -Cpb/gce At Various Sca...mentioning
confidence: 99%